1992
DOI: 10.1007/bf02050326
|View full text |Cite
|
Sign up to set email alerts
|

Is the volume retained after defecation a valuable parameter at defecography?

Abstract: The intention of this study was to correlate the retained volume at the end of defecography to certain defecographic findings and to the sense of incomplete emptying. In 170 defecographic series, the retained barium was estimated planimetrically. No particular defecographic finding determined a higher or lower amount of remaining volume, and the sense of incomplete evacuation did not depend on the amount of retained volume. Thresholds of urge and perception on anorectal manometry did not differ between patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
2
5

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 16 publications
0
32
2
5
Order By: Relevance
“…However, it was of no clinical significance. Although few studies found that symptoms of obstruction were correlated to the diagnosis of rectoceles [15,16], most studies have failed to show any clear association between either the rectoceles depth or the completeness of emptying to clinical symptoms or outcome following surgical repair [17][18][19]. Despite there was no significant association between the size of the rectoceles and the clinical symptoms, contrast retaining rectoceles were more likely to be larger than nonretaining ones [17,20,21].…”
Section: Discussionmentioning
confidence: 96%
“…However, it was of no clinical significance. Although few studies found that symptoms of obstruction were correlated to the diagnosis of rectoceles [15,16], most studies have failed to show any clear association between either the rectoceles depth or the completeness of emptying to clinical symptoms or outcome following surgical repair [17][18][19]. Despite there was no significant association between the size of the rectoceles and the clinical symptoms, contrast retaining rectoceles were more likely to be larger than nonretaining ones [17,20,21].…”
Section: Discussionmentioning
confidence: 96%
“…17 This aside, the indication for surgical repair of rectoceles still remains unclear. Although rectocele size, 18 barium entrapment, 19,20 and the need for vaginal digitation in particular are often cited, there is minimal evidence that these factors affect overall clinical outcome after repairs, however they are performed. [21][22][23] Moreover, there are few studies assessing incontinence as a principal symptom in patients presenting with rectocele.…”
Section: Discussionmentioning
confidence: 96%
“…Small rectoceles (<2 cm) are common even in the healthy population and may actually be a normal anatomic variant secondary to obstetric injury, trauma, and advanced age [10,[14][15][16][17][18]. Only 23%-27% of unselected patients with rectocele on physical examination have symptoms involving difficult evacuation [19,20].…”
Section: Discussionmentioning
confidence: 99%